Prognostic Factors and Clinical Characteristics of Duodenal Adenocarcinoma With Survival: A Retrospective Study - Sun, Huapeng; Liu, Yi; Lv, Long; Li, Jingwen; Liao, Xiaofeng; Gong, Wei (Frontiers in Oncology, 2021)
Background To evaluate the clinical risk factors that influence the overall survival in patients with duodenal adenocarcinoma (DA) after tumor resection. Methods This study retrospectively analyzed 188 patients who underwent tumor resection for DA between January 2005 and June 2020 at Xiangyang Central Hospital. Results The median survival of the patients who underwent resectional operation was 54 months, longer than of those who underwent palliative surgery (20.8 months) (2,916.17; 95% CI, 916.3−9,280.5; p < 0.001). Survival of non-ampullary duodenal carcinoma patients (50.3 months; 95% CI, 39.7−61.8) was similar to that of ampullary duodenal carcinoma patients (59.3 months; 95% CI, 38.6−66.7) but was significantly better than that of papillary adenocarcinoma patients (38.9 months; 95% CI, 29.8−54.8; p = 0.386). Those with intestinal-type ductal adenocarcinomas had a longer median overall survival than those with the gastric type (61.8 vs. 46.7 months; p < 0.01) or pancreatic type (32.2 months; p < 0.001). Clinical DA samples had significantly diverse expressions of ATG12, IRS2, and IGF2. Higher expressions of the ATG12 and IRS2 proteins were significantly correlated with worse survival. Multivariate Cox regression analysis revealed that lymph node metastasis (hazard ratio (HR), 6.44; 95% CI, 3.68−11.27; p < 0.0001), margin status (HR, 4.94; 95% CI, 2.85−8.54; p < 0.0001), and high expression of ATG12 (HR, 1.89; 95% CI, 1.17−3.06; p = 0.0099) were independent prognostic factors negatively associated with survival in patients undergoing curative resection. There was no survival difference between the groups with ampullary, non-ampullary, and papillary adenocarcinomas treated with adjuvant chemotherapy (p = 0.973). Conclusion Gastric/pancreatic type, high expression of ATG12, lymph node metastases, and margin status were negative prognosticators of survival in patients with DAs than in those with tumor anatomical location. Curative resection is the best treatment option for appropriate patients.